2019
DOI: 10.1007/s12192-018-0950-x
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp70/J-protein machinery of the African trypanosome, Trypanosoma brucei

Abstract: The etiological agent of the neglected tropical disease African trypanosomiasis, Trypanosoma brucei, possesses an expanded and diverse repertoire of heat shock proteins, which have been implicated in cytoprotection, differentiation, as well as progression and transmission of the disease. Hsp70 plays a crucial role in proteostasis, and inhibition of its interactions with co-chaperones is emerging as a potential therapeutic target for numerous diseases. In light of genome annotations and the release of the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 142 publications
(240 reference statements)
0
30
0
Order By: Relevance
“…Both proteins cooperate with the bacterial DnaK/DnaJ/GrpE (KJE) system, which is highly homologous to the mitochondrial Hsp70 system [51], and their chaperone-active reduced forms maintain client proteins in a refolding-competent conformation. An in silico survey of the Hsp70/J-protein machinery of African trypanosomes revealed 12 putative Hsp70 proteins and 67 putative J-proteins [64]. Many of these proteins were predicted or experimentally shown to be localized in the mitochondrion.…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins cooperate with the bacterial DnaK/DnaJ/GrpE (KJE) system, which is highly homologous to the mitochondrial Hsp70 system [51], and their chaperone-active reduced forms maintain client proteins in a refolding-competent conformation. An in silico survey of the Hsp70/J-protein machinery of African trypanosomes revealed 12 putative Hsp70 proteins and 67 putative J-proteins [64]. Many of these proteins were predicted or experimentally shown to be localized in the mitochondrion.…”
Section: Discussionmentioning
confidence: 99%
“…In Leishmania and Trypanosoma cruzi , heat shock proteins have been shown to play an essential role in stress-induced stage differentiation and are important for disease progression and transmission [4–5], making this protein family an attractive chemotherapeutic target. The completion of the Trypanosoma brucei ( T. brucei ) genome has expedited transcriptome and proteome analyses and revealed that the extracellular parasite has an expanded and diverse Hsp70 and J-protein complement, with the parasite possessing cytosolic Hsp70 members that display atypical Hsp70 features [6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent in silico investigation revealed that the T. brucei genome was found to encode 12 members of the Hsp70 superfamily, with 8 members from the Hsp70/HSPA family and 4 Hsp110/HSPH family members [6]. The same study identified 67 putative J-proteins, with 5 type I J-proteins [6]. Phenotypic knockdown of T. brucei genes using RNAi, conducted by Alsford and colleagues [21], demonstrated that the Hsp70/J-protein machinery plays a prominent role in trypanosome biology, as the loss of certain members of these protein families impacted the survival and fitness of the parasite at various stages of its life cycle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations